Interrogating the Role of the Two Distinct Fructose-Bisphosphate Aldolases of Bacillus methanolicus by Site-Directed Mutagenesis of Key Amino Acids and Gene Repression by CRISPR Interference - Schultenkämper, Kerstin; Gütle, Desirée D.; López, Marina Gil; Keller, Laura B.; Zhang, Lin; Einsle, Oliver; Jacquot, Jean-Pierre; Wendisch, Volker F. (Frontiers in Microbiology, 2021)
The Gram-positive Bacillus methanolicus shows plasmid-dependent methylotrophy. This facultative ribulose monophosphate cycle methylotroph possesses two fructose bisphosphate aldolases with distinct kinetic properties. The chromosomally encoded FBAC is the major glycolytic aldolase. The gene for the major gluconeogenic aldolase FBAP is found on the natural plasmid pBM19 and is induced during methylotrophic growth. The crystal structures of both enzymes were solved at 2.2 Å and 2.0 Å, respectively, and they suggested amino acid residue 51 to be crucial for binding FBP as substrate and amino acid residue 140 for active site zinc atom coordination. As FBAC and FBAP differed at these positions, site-directed mutagenesis was performed to exchange one or both amino acid residues of the respective proteins. The aldol cleavage reaction was negatively affected by the amino acid exchanges that led to a complete loss of glycolytic activity of FBAP. However, both FBAC and FBAP maintained gluconeogenic aldol condensation activity and the amino acid exchanges improved the catalytic efficiency of the major glycolytic aldolase FBAC in gluconeogenic direction at least three-fold. These results confirmed the importance of the structural differences between FBAC and FBAP concerning their distinct enzymatic properties. In order to investigate the physiological roles of both aldolases, the expression of their genes was repressed individually by CRISPRi. The fbaC RNA levels were reduced by CRISPRi, but concomitantly the fbaP RNA levels were increased. Vice versa, a similar compensatory increase of the fbaC RNA levels was observed when fbaP was repressed by CRISPRi. In addition, targeting fbaP decreased tktP RNA levels since both genes are cotranscribed in a bicistronic operon. However, reduced tktP RNA levels were not compensated for by increased RNA levels of the chromosomal transketolase gene tktC.